Dihydroartemisinin targets the miR-497-5p/SOX5 axis to suppress tumor progression in non-small cell lung cancer - Qing-Hua Yin; Qiang Zhou; Jian-Bing Hu; Jie Weng; Er-Dong Shen; Fang Wen; Song-Lian Liu; Lei-Lan Yin; Ya-Jun Tong; Ling Long; Ke-Wei Tang; Si-Te Bai; et al. (Frontiers in Pharmacology)
IntroductionNon-small cell lung cancer (NSCLC) remains a lethal malignancy with limited therapeutic options. Although dihydroartemisinin (DHA) exhibits anticancer properties, its mechanisms in NSCLC are incompletely understood. This study investigated the role of the miR-497-5p/SOX5 axis in mediating DHA’s effects on NSCLC.MethodsIn vitro experiments utilized A549 and H1299 cells treated with DHA (50 μM). Proliferation, migration, invasion, and apoptosis were assessed. miR-497-5p and SOX5 expression was modulated via genetic silencing. In vivo, A549 xenograft tumor growth in mice was evaluated under DHA treatment (25/50 mg/kg).ResultsDHA significantly suppressed proliferation, migration, and invasion while inducing apoptosis in vitro. Mechanistically, DHA upregulated miR-497-5p and downregulated SOX5—overexpressed in clinical NSCLC. Silencing miR-497-5p attenuated DHA’s effects and increased SOX5, whereas SOX5 knockdown reversed miR-497-5p inhibition. In vivo, DHA dose-dependently inhibited tumor growth with miR-497-5p elevation and SOX5 suppression, effects abrogated by miR-497-5p inhibition but rescued by SOX5 knockdown.DiscussionDHA exerts antitumor activity by activating the miR-497-5p/SOX5 axis, revealing a novel mechanism. Bridging efficacious in vitro concentrations with clinically achievable dosing remains essential for therapeutic translation.